Aplikasi Menulis Huruf Arab Dengan Teknologi Gestures Berbasis Android - Yogistina, Darari; Sutanto, Teguh; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Abstract: Learning writing letters arab media in general use book “Lembar kegiatan Belajar” (LKB), in the form of a pattern of dots forming letters in arabic but sometimes in LKB there is not tutorial of how to write letters arab. Book tended  to be informative and one direction. Interactive learning can be applied to one of them on android. It can replace the learning that is assessed to be inadequate to write basic Arabic letters.Applications write arabic letters android-based learning is an option to replace the media book, because there are some features that the introduction of the Arabic alphabet in the form of motion pictures that provide info manner of writing the Arabic alphabet and features a user exercises in writing the Arabic alphabet then the system will give you the info is true or false. Matching gestures using $N. Methods $N will perform template matching gestures or point coordinates are specified by the user writing input. In addition, there is a quiz. Applications written with the Arabic alphabet gestures technologies built to show the procedure of writing the Arabic alphabet with animated motion picture in accordance with the rules. This application can also interact with humans, because applications can provide value information from the user to exercise.